Workplace-Oriented Research and Mentoring of Entreprenuers: Cooperation University-Industry - Hamburg, Ileana; O´Brien, Emma; Vladut, Gabriel (Archives of Business Research, 2018)
The benefits and longer impact of a strong cooperation university-industry particularly for entrepreneurs and small and medium-sized enterprises - SMEs - are known from different studies but it seems that measures in order to strength it are not sufficient. This paper explores the innovation barriers faced by small companies, challenges they face when collaborating with universities and explores if workplace research skills can potentially offer a method to enhance the absorptive capacity of small companies. Some forms of mentoring for entrepreneurs, a definition of the relationship mentor-mentee are shortly presented. Example of projects with the participation of the authors and measures which are planned to be implemented to to improve cooperation university-industry are also given.